Using Waste from Food Cans as Electrode in Electrocoagulation for Wastewater Treatment - Soonsorn, Chanchanok; Khuanmar, Kulyakorn; Padungthon, Surapol; Weerayutsil, Panomchai (International Journal of Engineering and Technology, 2018)
Wastes from soda and milk cans which contain metals can be used as electrode in Electrocoagulation (EC) technique. The study used wastewater from dyeing and finishing process of textile factory. Both the electrodes made from soda cans and milk cans were compared to the conventional electrodes made from aluminium sheet. Characterization of aluminium (Al) element in electrode showed 67.28% in aluminium sheets, 4.99% in soda cans, and 0% in milk cans. Nevertheless, only milk cans contain iron (Fe) and tin (Sn) at 45.87% and 23.87%, respectively. Based on treatment efficiency in COD removal from the real wastewater, it turned out that the highest efficiency was from aluminium sheets, at 83.57%, whereas soda-can electrodes and milk-can electrodes were 80.71% and 71.14%, respectively. This could result from the fact that soda-can electrodes contain high percentage of aluminium while milk-can electrodes have no aluminium, leading to its low efficiency. Although Fe in milk can function as electrodes, the efficiency cannot be compared to electrodes made from soda cans. Therefore, soda cans make an efficient material for electrodes because of its high percentage of aluminium. Analysis of SEM images demonstrated compactly agglomerated sludge from aluminium electrodes and soda-can electrodes. The image from testing milk can material demonstrated in contrast loosely agglomerated sludge. It can be concluded that the use of electrodes containing aluminium produces relatively more effective sedimentation. Â Â Â Â Â Â